2022
DOI: 10.1111/nph.18416
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐omics framework reveals strawberry flavor genes and their regulatory elements

Abstract: Summary Flavor is essential to consumer preference of foods and is an increasing focus of plant breeding programs. In fruit crops, identifying genes underlying volatile organic compounds has great promise to accelerate flavor improvement, but polyploidy and heterozygosity in many species have slowed progress. Here we use octoploid cultivated strawberry to demonstrate how genomic heterozygosity, transcriptomic intricacy and fruit metabolomic diversity can be treated as strengths and leveraged to uncover fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 84 publications
(130 reference statements)
0
29
0
Order By: Relevance
“…Importantly, QTL mapping led to the characterization of FaOMT, an essential gene for the production of mesifurane (Zorrilla-Fontanesi et al, 2012). Results of GWAS studies from Florida breeding lines revealed the same QTL locations for many volatiles (Barbey et al, 2021;Fan et al, 2022). These association mapping studies uncovered genetic control of mesifurane but not furaneol.…”
Section: 1mentioning
confidence: 93%
See 3 more Smart Citations
“…Importantly, QTL mapping led to the characterization of FaOMT, an essential gene for the production of mesifurane (Zorrilla-Fontanesi et al, 2012). Results of GWAS studies from Florida breeding lines revealed the same QTL locations for many volatiles (Barbey et al, 2021;Fan et al, 2022). These association mapping studies uncovered genetic control of mesifurane but not furaneol.…”
Section: 1mentioning
confidence: 93%
“…Mesifurane abundance is dependent on an o‐methyl transferase gene ( FaOMT ) that has been functionally validated and mapped to chromosome 7D (Barbey et al., 2021; Zorrilla‑Fontanesi et al., 2012). Nonfunctional alleles are characterized by a 28 bp indel in the first exon that causes premature termination of transcription (Fan et al., 2022). There is also evidence that the locus discovered for furaneol on chromosome 1C also modulates mesifurane content (Barbey et al., 2021).…”
Section: Flavor‐affecting Metabolites and Their Genetic Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…A transcriptome analysis of Chinese pear showed high variation of gene expressions during the developmental phase of tissues and fruits ( Xie et al., 2013 ). In strawberry, a multiomics approach revealed the association of different genes regulating volatile organic compounds behind the flavor characteristics of its berries ( Fan et al., 2022 ). A comparative transcriptome analysis among several apple verities exhibited 34 genes regulating the anthocyanin contents which are associated with preferred appearance of apples ( El-Sharkawy et al., 2015 ).…”
Section: Omics Approach In Temperate Fruits and Nutsmentioning
confidence: 99%